2016
DOI: 10.1089/jwh.2015.5290
|View full text |Cite
|
Sign up to set email alerts
|

Unintended Pregnancy, Depression, and Hazardous Drinking in a Community-Based Sample of Sexual Minority Women

Abstract: Context: Unintended pregnancy is a stressful life event with important implications for women's health. Little research has examined sexual minority women's (SMW; lesbian, bisexual, mostly heterosexual) experiences of unintended pregnancy, and no studies have examined the relationship between unintended pregnancy, mental health, and negative coping behaviors in this population. Methods: We used the Chicago Health and Life Experiences of Women (CHLEW) Study (n = 454), a diverse sample of SMW, to examine the rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 70 publications
1
29
0
Order By: Relevance
“…This may be at least partly attributed to the fact that drinking before pregnancy recognition was specifically queried and included in our estimates, whereas national surveys do not specifically inquire about drinking after LMP but prior to pregnancy recognition. In this study, pregnant women seen in the SUD clinic had somewhat later pregnancy recognition (by approximately 2 weeks) compared to the general obstetrics population, which is consistent with other reports (Campo et al, 2010; Everett et al, 2016; Heil et al, 2011; Jones et al, 2011; Terplan et al, 2014; Than et al, 2005). Thus, higher alcohol consumption in pregnant women with SUD might, in part, be due to delayed pregnancy recognition.…”
Section: Discussionsupporting
confidence: 91%
“…This may be at least partly attributed to the fact that drinking before pregnancy recognition was specifically queried and included in our estimates, whereas national surveys do not specifically inquire about drinking after LMP but prior to pregnancy recognition. In this study, pregnant women seen in the SUD clinic had somewhat later pregnancy recognition (by approximately 2 weeks) compared to the general obstetrics population, which is consistent with other reports (Campo et al, 2010; Everett et al, 2016; Heil et al, 2011; Jones et al, 2011; Terplan et al, 2014; Than et al, 2005). Thus, higher alcohol consumption in pregnant women with SUD might, in part, be due to delayed pregnancy recognition.…”
Section: Discussionsupporting
confidence: 91%
“…Eligibility criteria for these additional sexual minority participants in the longitudinal CHLEW study included lesbians who were between the ages of 18 and 24, lesbians of any age who belonged to a racial or ethnic minority group and, bisexually identified women of any age group or racial or ethnic background. 18 This additional sample was recruited using an adaptation of respondent-driven sampling. 19 As the new cohort recruitment was specifically designed to oversample Black, Latina, and younger lesbians (ages [18][19][20][21][22][23][24], as well as women who identified as bisexual, participants in the third wave of data collection differed from the earlier cohorts on these factors (younger, more racial and ethnic minority SMW, and more bisexual women, analyses not shown).…”
Section: Participantsmentioning
confidence: 99%
“…18 This additional sample was recruited using an adaptation of respondent-driven sampling. 19 As the new cohort recruitment was specifically designed to oversample Black, Latina, and younger lesbians (ages [18][19][20][21][22][23][24], as well as women who identified as bisexual, participants in the third wave of data collection differed from the earlier cohorts on these factors (younger, more racial and ethnic minority SMW, and more bisexual women, analyses not shown). This third wave of participants will be included in future longitudinal follow-ups and analyses.…”
Section: Participantsmentioning
confidence: 99%
“…Previous research has demonstrated an increased risk of alcohol use and unintended pregnancy, 11,26,27 although alcohol exposure is often assessed as patterns of heavy or binge drinking. 11,27 Studies have also reported an association between preconception and prenatal smoking and unwanted pregnancy 15,28 ; however, we observed no association with tobacco smoking and unwanted pregnancy but rather an increased likelihood of undesired or ambivalent pregnancy, and Bold text indicates a statistical significance with a p-value of <0.05; Variables including employment, age, gestational age, education, marital status, race/ethnicity, parity, chronic medical problem, language, previous abortion, previous miscarriage, history of depression, history of anxiety, other substance use in addition to exposure of interest, and recruitment site evaluated as potential confounders in multivariable modeling using backwards selection.…”
Section: Discussionmentioning
confidence: 99%